A Dynamical Gravitational Wave Source in a Dense Cluster. (19th August 2016) - Hurley, Jarrod R.; Sippel, Anna C.; Tout, Christopher A.; Aarseth, Sverre J.
Abstract: Making use of a new N -body model to describe the evolution of a moderate-size globular cluster, we investigate the characteristics of the population of black holes within such a cluster. This model reaches core-collapse and achieves a peak central density typical of the dense globular clusters of the Milky Way. Within this high-density environment, we see direct confirmation of the merging of two stellar remnant black holes in a dynamically formed binary, a gravitational wave source. We describe how the formation, evolution, and ultimate ejection/destruction of binary systems containing black holes impacts the evolution of the cluster core. Also, through comparison with previous models of lower density, we show that the period distribution of black hole binaries formed through dynamical interactions in this high-density model favours the production of gravitational wave sources. We confirm that the number of black holes remaining in a star cluster at late times and the characteristics of the binary black hole population depend on the nature of the star cluster, critically on the number density of stars and by extension the relaxation timescale.